ORGANIZATIONAL CULTURE AND COMPETENCE TOWARDS TEACHER PERFORMANCE WITH WORK MOTIVATION AS A MEDIATION VARIABLE AT SMP NEGERI 4 GRESIK - Surya Yetni; Moh Agung Surianto; Eva Desembrianita; Muhammad Rosyihuddin (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2022)
This study aims to find out in depth about organizational culture, competence, on teacher performance mediated by motivation, which is at SMP Negeri 4 Gresik. The population and sample in this study were all teachers at SMP Negeri 4 Gresik, totaling 49 people, using a saturated sample, all members of the population were sampled. The data analysis tool uses the SmartPLS for windows program. Based on the results of the analysis, it was found that all hypotheses in this study can be accepted, directly organizational culture and competence have a positive and significant effect on performance and motivation. For the indirect effect of organizational culture and competence have a positive and significant effect on performance mediated by motivation.